Performance improvement of a centrifugal compressor for cogeneration - David F. Blanco-Patiño; Juliana Niño-Navia; Jorge I. Garcia-Sepulveda; César Nieto-Londoño (International Journal of Thermofluids)
This work presents the performance improvement of a centrifugal compressor designed for cogeneration applications. The study involves modifications to geometric parameters, including impeller and diffuser configurations, to enhance pressure ratio, temperature ratio, and overall efficiency using computational fluid dynamics to verify the improvement of those parameters. The study has examined the compressor’s behaviour under surge, design, and choke conditions, showcasing improved homogeneity, reduced low-velocity zones, and an extended operating range. The compressor maps are presented to graphically observe the impact of each proposed modification, facilitating the analysis of each of these and evaluating the performance under various operating conditions. The final compressor configuration exhibits notable improvements in key performance metrics, with pressure ratio, temperature ratio, and efficiency showing increases of 1.753%, 1.640%, and 1.760%, respectively.